2020
DOI: 10.1039/d0sc00757a
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional nanoprobe for targeting tumors and mitochondria with singlet oxygen generation and monitoring mitochondrion pH changes in cancer cells by ratiometric fluorescence imaging

Abstract: A multifunctional nanoprobe with singlet oxygen generation that can target tumors and mitochondria was developed for photodynamic therapy of tumors and monitoring mitochondrion pH changes in cancer cells by ratiometric fluorescence imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The FT-IR spectra was used to further study the possible chemical bonds between CDs and wood. As shown in Figure S6 in the Supporting Information, compared with CDs, CDs@wood exhibits a wider vibration band at 3400 cm –1 because of the overlap between −OH and N–H groups, proving the chemical hybridization of CDs and wood . In addition, the peak of wood at 1660 cm –1 assigned to the −CO vibration band blueshifts and widens in the CDs@wood, suggesting that the CDs fully grafted onto the wood matrix .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The FT-IR spectra was used to further study the possible chemical bonds between CDs and wood. As shown in Figure S6 in the Supporting Information, compared with CDs, CDs@wood exhibits a wider vibration band at 3400 cm –1 because of the overlap between −OH and N–H groups, proving the chemical hybridization of CDs and wood . In addition, the peak of wood at 1660 cm –1 assigned to the −CO vibration band blueshifts and widens in the CDs@wood, suggesting that the CDs fully grafted onto the wood matrix .…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure S6 in the Supporting Information, compared with CDs, CDs@ wood exhibits a wider vibration band at 3400 cm −1 because of the overlap between −OH and N−H groups, proving the chemical hybridization of CDs and wood. 56 In addition, the peak of wood at 1660 cm −1 assigned to the −CO vibration band blueshifts and widens in the CDs@wood, suggesting that the CDs fully grafted onto the wood matrix. 57 Moreover, the expansion vibration of the C−C and C−O single bond and the absorption of C−H bending vibration in the range of 1000− 400 cm −1 were significantly enhanced for CDs@wood, further showing that CDs are introduced into the wood matrix through chemical bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Although many mitochondria-targeting nanoparticles have been used to enhance cancer treatment, the leakage of drugs in cytoplasm and lysosome is challenging for all researchers when the therapeutic nanoparticles get inside the cancer cells ( Wong and Choi, 2015 ; Xiong et al, 2016 ; Huang et al, 2021 ). As we know, the pH value of tumor cell mitochondria is approximately 8.0 ( Matsuyama et al, 2000 ; Zhao et al, 2020 ). Thus, Tan et al (2018) constructed a mitochondrial alkaline-responsive drug delivery system loading an acidic drug, which could not only facilitate fast drug release in mitochondria to improve the anticancer efficiency, but also decrease the nonspecific toxicity observably by means of reducing the drug leakage in the neutral cytoplasm and acidic lysosome.…”
Section: Mitochondria Targeting With the Aid Of Multifunctional Nanosystemsmentioning
confidence: 99%
“… 11,12 This is because multicolor fluorescence carbon dots have attractive application prospects in cell fluorescence bioimaging, which can track cellular changes (direct correlation with diseases) in organisms. 13–15 Wang et al reported and prepared tricolor CDs from isomers, 16 and proved that high nitrogen doping, bigger particle sizes and narrower band gaps induced the red shift of fluorescence emission from CDs. Zhang et al 17 synthesized full-color carbon dots based on a doping strategy and the possible ET mechanisms were proposed.…”
Section: Introductionmentioning
confidence: 99%